Rola regulacji prawnych w kształtowaniu treści gier i mechanizmów ich promocji na przykładzie wybranych zagadnień ochrony konsumentów - Makuch, Szymon (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The aim of the article is to discuss in brief the role of legal regulations in shaping the content of games and the mechanisms for their promotion, using selected consumer protection issues as examples. The subject became particularly high-profile in Poland after the release of Cyberpunk 2077, but has been discussed many times around the world, and in recent years there has been a visible trend of many consumer protection authorities to look more closely at the gaming industry and react to bad practices in this area. The article cites some key examples, but also potential practical implications for publishers.